Sibling Rivalry in the Perspective of Islamic Education - Sardi Mustaupa (Universitas Darunnajah Jakarta, Indonesia, 2024)
This study aims to delve into the concept of sibling Rivalry in the Qur'an using a scientific approach. Siblinghood is a profound and essential value in Islamic teachings, serving as the foundation for interpersonal relationships within society. This research focuses on the analysis of Qur'anic verses that depict and discuss various aspects of siblinghood. The research methodology involves textual analysis of relevant verses, considering the historical and cultural context at the time of revelation. The findings indicate that the Qur'an emphasizes the significance of siblinghood as a basis for creating a just and harmonious society. Specific verses provide guidance on the rights and responsibilities among siblings, offering insights into the moral values that should be upheld in these relationships. This analysis also reveals that siblinghood in the Qur'an is not merely biological but encompasses spiritual and moral dimensions as well. The concept teaches solidarity, mutual assistance, and love among siblings as manifestations of devotion to Allah. Therefore, a profound understanding of the concept of siblinghood in the Qur'an can serve as a foundation for building a society characterized by compassion and justice. This research contributes to the scholarly understanding of the concept of siblinghood in the Qur'an and provides a new perspective on its practical implementation in daily life. The implications of this research can be used as a basis for developing educational and social programs aimed at strengthening the values of siblinghood in Muslim communities. Keywords: sibling Rivalry, Islamic Values, Solidarity